The Role of Community Library Rumah Asa in Empowerment of Communities in Karangkajen Yogyakarta - Hayati, Nurul (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2020)
Community Library is an institution that provides various types of learning materials needed by the community. TBM As a place for organizing the ability to read and learn, as well as a place to get information for the community. One of the TBMs carrying out these activities is Rumah Asa TBM. In addition to disseminating information, TBM Rumah Harapan also plays a role in community empowerment. This paper describes community empowerment carried out by Taman Bacaan Masyarakat. To obtain these data this paper uses a literature study in the form of conceptual studies. The role of TBM Rumah Asa in community empowerment includes hand skills for mothers, asakura shops, mukena asakura, and Eco.J print. Keywords: Community Library, Community Empowerment